Public relations strategy of rsud dr. H. Mohammad rabain in improving the quality of public services In muara enim district - Cheny Wulan Sari; Sulbahri Madjir; Harun Samsuddin (Journal of Indonesian Management, 2023)
The author conducted research at Public Relations Hospital Dr. H. Mohamad Rabain Research with the aim of Knowing and Analyzing the Public Relations Strategy of RSUD Dr. H. Mohamad Rabain in Improving the Quality of Public Services and to Know and Analyze the Challenges and Obstacles of Public Relations of RSUD Dr. H. Mohamad Rabain in Improving the Quality of Public Services. The type of research used by the author in this research is field research using a qualitative approach, namely a research approach that produces descriptive data in the form of written or spoken words from the objects or subjects observed from which conclusions are then drawn. Researchers try to understand the phenomena experienced by research subjects and conduct studies on field studies. Qualitative research is also a form of research that aims to describe existing problems that occur in the research object. Public Relations Strategy of RSUD Dr. H. Mohamad Rabain In Improving the Quality of Public Services, namely: Growing public awareness of the products and services provided. Build public trust in the image of the Hospital or the benefits of the products and services offered. Encouraging enthusiasm for understanding the uses and benefits of a product and services provided. Reducing promotional costs for commercial costs, both in electronic media and print media and so on in order to achieve cost efficiency. Commitment to improving service to consumers, including the costs of resolving complaints and so on in order to achieve customer satisfaction. Continuously communicate through public relations media about activities and work programs related to social care, in order to achieve positive publications in the eyes of the community/public. Building and maintaining the image of the hospital or its products and services, both in terms of quantity and quality of services provided to consumers and working proactively to deal with negative events that may arise in the future.